(untitled) (Південний архів (історичні науки), 2021)
Purpose. The article considers the process of forming the image of the military human during the military expansion of the USSR in the late 1930’s on the basis of materials of individual publications of Soviet military periodicals of that time. The military press of this period is characterized by a variety of publications: from ordinary army newspapers to political publications for the command and military-political staff of the Red Arme and the USSR Navy. All publications had a similar structure and content, so the source base is the materials published in the newspaper "Krasnaya Zvezda" and the periodical "Propagandist and agitator of the Red Army", which contain significant and interesting material on all aspects of social and political image of the Soviet soldier in this period. Results and scientific novelty of the study. It was found that the process of forming the image of the military, well reflected in the Soviet military-political periodicals at the beginning of the Soviet military expansion had the following features. the social image was formed on the basis of the needs of the then foreign and domestic policy of the Soviet state and reflected all the claims of the Soviet system to world domination. The task of the military press was to depict the successes in creating the image of a special, different from the Western model of the soldier. The tendency to glorify a soldier of the revolutionary army continues, attention is focused on the connection of generations, comparisons are made with the heroes of the past, even with epic heroes.This points to attempts to prove the legitimacy of claims to the entire military historical heritage, to all those territories that were once conquered by the Russian army (contrary to the very Bolshevik position on the unjust and aggressive nature of the wars once waged by the Russian tsarist army). The image of an impeccable soldier with a clear understanding of his historical mission as a liberator, a victor, because the wars in which the USSR entered in 1939 were a priori defined as legitimate, just from the point of view of the Bolshevik dogma of war just and unjust. The image of the military human in the Soviet consciousness of both the average citizen and the soldier himself, which, in turn, were formed under the significant influence of propaganda, which was important for both the Red Army and society. The general social image of the invincible army, the impeccable fighter of the Red Army, gradually intensified, in a way uniting the images of the leaders of the party and the country with the image of an ordinary soldier, which became part of the mythologizing Soviet reality. All the above provisions make it possible to note that the military-political press of the end 1930’s, in the context of military conflicts, although quite standardized, at that time successfully fulfilled its role in building a stable social image of the Soviet military. . Already at this time there is a certain evolution of the image military human. The public image of a soldier of the revolutionary Red Army is transformed into the image of a liberating soldier, a defender of peace throughout the world. This clearly shows the traditional for the empire awareness of its messianic role in the world, on the basis of which was built a new form, but essentially old social image of the military human.